(untitled) (Research, Society and Development, 2021)
Autism spectrum disorder (ASD) is a disorder that affects children’s neurodevelopment and makes their capacity for social and intellectual interaction and behavior less developed. The aim of this study was to show how epigenetic disorders can contribute to the emergence of autistic children, demonstrating how essential it is to carry out scientific research and seek to understand the epigenetic characteristics that lead to the development of ASD. The study seeks to carry out an integrative literature review and has as descriptors: "autistic spectrum disorder and epigenetic disorders", "autism", "epigenetic disorders", "autism spectrum disorder and epigenetic disorders", "autism", "autism spectrum disorder”, “epigenetics disorders”, the databases consulted were Pubmed, Scientific Electronic Library Online (Scielo) and Academic Google. Studies show that ASD is characterized as a multifactorial inheritance disorder and that environmental factors, whether independent or in conjunction with epigenetic factors, increase the risk of this condition. We conclude that epigenetic alterations are associated with autism, as well as the behavioral and histological consequences of this disorder.